Release of Platelet-Derived Sphingosine-1-Phosphate Involves Multidrug Resistance Protein 4 (MRP4/ABCC4) and Is Inhibited by Statins - Vogt, Katja; Mahajan-Thakur, Shailaja; Wolf, Robert; Bröderdorf, Susanne; Vogel, Conny; Böhm, Andreas; Ritter, Christoph A.; Gräler, Markus; Oswald, Stefan; Greinacher, Andreas; Kroemer, Heyo K.; Jedlitschky, Gabriele; Rauch, Bernhard H. (Thrombosis and Haemostasis, 2018)
Sphingosine-1-phosphate (S1P) is a potent lipid mediator released from activated platelets by an adenosine triphosphate (ATP)-dependent export mechanism. A candidate transport protein is the multidrug resistance protein 4 (MRP4/ABCC4), an ATP-dependent transporter highly expressed in platelets. Furthermore, several statins are known to affect platelet functions and exhibit antithrombotic properties. This study determines the involvement of MRP4 in the transport of S1P and a possible interference by statins. Transport studies in membrane vesicles of Sf9 cells containing recombinant human MRP4 revealed that MRP4 mediates ATP-dependent transport of fluorescein- and tritium-labelled S1P. Also, ATP-dependent S1P transport in platelet membrane vesicles containing endogenous MRP4 was inhibited by the MRP inhibitor MK571 and the MRP4-selective compound Ceefourin-1. Confocal microscopy using fluorescein-labelled S1P as well as boron-dipyrromethene (BODIPY)-labelled sphingosine indicated association of S1P and MRP4 in human platelets. In MRP4-deficient mice, agonist-induced S1P secretion was reduced compared with matched wild-type C57Bl/6 mice and platelet S1P concentrations were lower. Fluvastatin and rosuvastatin interfered with MRP4 function inhibiting ATP-dependent cGMP (cyclic guanosine monophosphate) uptake into MRP4-containing vesicles, inhibited MRP4-mediated S1P transport in vitro and significantly attenuated endogenous S1P release from agonist-activated platelet ex vivo. These data suggest that release of S1P from platelets depends on MRP4 and statins can interfere with this transport process. Potentially, this may be relevant for the pleiotropic anti-inflammatory effects of statins and their effect on modulating atherothrombosis.
Keywords: sphingosine-1-phosphate; MRP4; platelets; statins; ABC transporter